EFFECT OF MANAGEMENT PRACTICES FOR GREEN LAND AT Al-ZAWRA AND BAGHDAD ISLAND PARK IN SOME SOIL PRPOPERTIES USING GEOTECHNOLOGIES - Alawji , Zainab; Almashhadani , Haleema (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to investigate variations in some soil properties characteristics of green spaces soils within Baghdad Island Park and Al-Zawraa parks in Baghdad province, Iraq, due to the variation in used management methods. Soil samples were obtained from 22 locations in each park at 0-30 cm depth using a GARMEN GPS device (Oregon650t). Satellite images (Landsat 8 satellite and an OLI sensor) were captured with a 30 x 30 m2 spatial resolution. The research aims to study the effect of the management method of the two parks (BID and Al-Zawra) on some soil pedological characteristics. The results showed a variation in the spatial distribution of the soil texture classes at each park due to particle size distribution variation of the soil classes. The sand particle was dominant, followed by silt and clay, with a variation in the spatial distribution of the soil content of calcium carbonate equivalent and organic matter content. A decrease was recorded in the content of gypsum. The observed variation in the electrical conductivity values is attributed to the irrigation system used and similar management practices for each park’s soil. Irrigation and fertilization systems are in correct and require management follow-up to reach green spaces that are fresh and soft in color. Using the NPK Nutrient Readiness Index for green spaces in parks showed that their soils had a low content of available nitrogen and potassium and medium range of available phosphorus.